Discourse-related expletives: Challenges and opportunities - Booth, Hannah; Groothuis, Kim A. (Open Linguistics, 2024)
Recent research has highlighted the existence of expletive(-like) elements in various languages that are related to discourse, serving as fillers for designated topic/focus positions and/or contributing specific discourse–pragmatic effects. Such elements pose a number of challenges and opportunities, both for our overall conception of expletives and for our understanding of the syntax–discourse interface, although work in this area to date has mainly focused on the phenomenon in individual varieties. In this study, we critically survey the current state-of-the art on this topic and discuss four main areas where we see particular challenges and opportunities for research: (i) categories and definitions, (ii) typological correlations, (iii) theoretical modelling and (iv) language change. Overall, this article brings together a broad array of empirical findings and theoretical approaches on the phenomenon of discourse-related expletives and highlights the many avenues for future work in this area.